Transcriptome Analysis of Genes Involved in Cold Hardiness of Peach Tree (Prunus persica) Shoots during Cold Acclimation and Deacclimation - Yu, Duk Jun (Genes (Basel), 2020)
We analyzed the transcriptomes in the shoots of five-year-old ‘Soomee’ peach trees (Prunus persica) during cold acclimation (CA), from early CA (end of October) to late CA (middle of January), and deacclimation (DA), from late CA to late DA (middle of March), to identify the genes involved in cold hardiness. Cold hardiness of the shoots increased from early to late CA, but decreased from late CA to late DA, as indicated by decreased and increased the median lethal temperature (LT(50)), respectively. Transcriptome analysis identified 17,208 assembled transcripts during all three stages. In total, 1891 and 3008 transcripts were differentially expressed with a |fold change| > 2 (p < 0.05) between early and late CA, and between late CA and late DA, respectively. Among them, 1522 and 2830, respectively, were functionally annotated with gene ontology (GO) terms having a greater proportion of differentially expressed genes (DEGs) associated with molecular function than biological process or cellular component categories. The biochemical pathways best represented both periods from early to late CA and from late CA to late DA were ‘metabolic pathway’ and ‘biosynthesis of secondary metabolites’. We validated these transcriptomic results by performing reverse transcription quantitative polymerase chain reaction on the selected DEGs showing significant fold changes. The relative expressions of the selected DEGs were closely related to the LT(50) values of the peach tree shoots: ‘Soomee’ shoots exhibited higher relative expressions of the selected DEGs than shoots of the less cold-hardy ‘Odoroki’ peach trees. Irrespective of the cultivar, the relative expressions of the DEGs that were up- and then down-regulated during CA, from early to late CA, and DA, from late CA to late DA, were more closely correlated with cold hardiness than those of the DEGs that were down- and then up-regulated. Therefore, our results suggest that the significantly up- and then down-regulated DEGs are associated with cold hardiness in peach tree shoots. These DEGs, including early light-induced protein 1, chloroplastic, 14-kDa proline-rich protein DC2.15, glutamate dehydrogenase 2, and triacylglycerol lipase 2, could be candidate genes to determine cold hardiness.